Adolescent Mental Health Therapy through the Application of Islamic Religious Education - Sakinah, Dahlia Nur; Fuad, Ai Fatimah Nur; Darraz, Muhammad Abdullah; Nuraeni, Heni Ani (Jurnal Pendidikan Amartha, 2024)
The aim of this research is to explore mental health therapy through aspects of religious life. This research is included in the type of descriptive qualitative research. Data collection was carried out through observation, interviews and document analysis. The research subjects involved the school principal, Islamic Religious Education (PAI) teacher, Guidance Counseling (BK) teacher, and two students. The data analysis techniques used include data reduction, data presentation and verification. Based on research, it is known that religious life can be a mental health therapy for students at SMK N 38 Jakarta. Religious activities carried out at the school include dhuha prayers, dhuhur prayers in congregation and reading yasin. From the results of interviews with students, the author found that participating in religious activities carried out by the school provided comfort to the souls of students at SMK N 38 Jakarta.